Aplicação de técnicas estatísticas para avaliação de desempenho e confiabilidade de estações de tratamento de água - Livia Duarte Ventura Melo (2014)
This paper proposes a methodology for evaluating the performance of treatment plants (WTP), considering unusual statistical tools in the area, applied to six water treatment stations. A characterization of the quality of raw water and treated water in the period 2001-2011, considering the data of turbidity, apparent color, concentrations of residual chlorine and fluoride, pH and total coliforms was performed. Statistical analyzes were performed for the dry and rainy seasons and considered several steps: assessing individual performance of the various treatment plants, considering the standards of potability and quality targets for treated water; comparative study of the performance of various treatment technologies analyzed; comparative analysis of the performance of water treatment plants, according to the size, reliability analysis of treatment plants. On the WTPs performance comparation as a function of technology adopted, the double filtration showed smaller values of turbidity of the treated water than the others process. The color, however, was more efficiently removed by double filtration technology than by the conventional, flotation followed by direct filtration, but it was equivalent to direct filtration process. Parameter for the residual chlorine, it was observed that all treatment technologies are significantly different, both in the dry season and in the rainy season. Performance evaluation of treatment plants grouped by size showed that the WTPs Midsize had the lowest turbidity and color in both periods. The results of the reliability analysis showed that the mean turbidity values observed in the treated water for almost all WTPs would be insufficient to ensure 95% compliance with the standards of 0,3 and 0,5 NTU. As the patterns become more flexible, WTPs can serve them and, in the case of default of 5,0 NTU, all WTPs easily guarantee the percentage of 95 % attendance. All water treatment plants meet the goal imposed by brazilian Ordinance 2914/2011, which defines values less than 15,0 HU for the color parameter.